Corrigendum: Broad distribution and high proportion of protein synthesis active marine bacteria revealed by click chemistry at the single cell level - Ty J. Samo; Steven Smriga; Francesca Malfatti; Byron P. Sherwood; Farooq Azam (Frontiers in Marine Science, 2014)

Broad distribution and high proportion of protein synthesis active marine bacteria revealed by click chemistry at the single cell level - Ty J. Samo; Steven Smriga; Francesca Malfatti; Byron P. Sherwood; Farooq Azam (Frontiers in Marine Science, 2014)

Gradients of coastal fish farm effluents and their effect on coral reef microbes - Melissa Garren; Steven Smriga; Farooq Azam (Environmental Microbiology, 2008)
Summary Coastal milkfish ( Chanos chanos ) farming may be a source of organic matter enrichment for coral reefs in Bolinao, Republic of the Philippines. Interactions among microbial communities associated with the water column, corals and milkfish feces can provide insight into the ecosystem's response to enrichment. Samples were collected at sites along a transect that extended from suspended milkfish pens into the coral reef. Water was characterized by steep gradients in the concentrations of dissolved organic carbon (70–160 μM), total dissolved nitrogen (7–40 μM), chlorophyll a (0.25–10 μg l −1 ), particulate matter (106–832 μg l −1 ), bacteria (5 × 10 5 −1 × 10 6 cells ml −1 ) and viruses (1–7 × 10 7 ml −1 ) that correlated with distance from the fish cages. Particle‐attached bacteria, which were observed by scanning laser confocal microscopy, increased across the gradient from Acinetobacter sp. and Ralstonia sp. Such patterns raise the question of whether bacteria might be transported from the fish pens to corals or if microenvironments at the fish pens and on the corals select for the same phylotypes. Understanding the underlying mechanisms of effluent–coral interactions will help predict the ability of coral reef ecosystems to resist and rebound from organic matter enrichment.

Indirect effects of algae on coral: algae‐mediated, microbe‐induced coral mortality - Jennifer E. Smith; Morrigan Shaw; Rob A. Edwards; David Obura; Olga Pantos; Enric Sala; Stuart A. Sandin; Steven Smriga; Mark Hatay; Forest L. Rohwer (Ecology Letters, 2006)
Declines in coral cover are generally associated with increases in the abundance of fleshy algae. In many cases, it remains unclear whether algae are responsible, directly or indirectly, for coral death or whether they simply settle on dead coral surfaces. Here, we show that algae can indirectly cause coral mortality by enhancing microbial activity via the release of dissolved compounds. When coral and algae were placed in chambers together but separated by a 0.02 μ m filter, corals suffered 100% mortality. With the addition of the broad‐spectrum antibiotic ampicillin, mortality was completely prevented. Physiological measurements showed complementary patterns of increasing coral stress with proximity to algae. Our results suggest that as human impacts increase and algae become more abundant on reefs a positive feedback loop may be created whereby compounds released by algae enhance microbial activity on live coral surfaces causing mortality of corals and further algal growth.

Trophic regulation of Vibrio cholerae in coastal marine waters - Alexandra Z. Worden; Michael Seidel; Steven Smriga; Arne Wick; Francesca Malfatti; Douglas Bartlett; Farooq Azam (Environmental Microbiology, 2006)
Summary Cholera disease, caused by the bacterium Vibrio cholerae , afflicts hundreds of thousands worldwide each year. Endemic to aquatic environments, V. cholerae 's proliferation and dynamics in marine systems are not well understood. Here, we show that under a variety of coastal seawater conditions V. cholerae remained primarily in a free‐living state as opposed to attaching to particles. Growth rates of free‐living V. cholerae (µ: 0.6–2.9 day −1 ) were high (similar to reported values for the bacterial assemblages; 0.3–2.5 day −1 ) particularly in phytoplankton bloom waters. However, these populations were subject to heavy grazing‐mortality by protozoan predators. Thus, grazing‐mortality counterbalanced growth, keeping V. cholerae populations in check. Net population gains were observed under particularly intense bloom conditions when V. cholerae proliferated, overcoming grazing pressure terms in part via rapid growth (> 4 doublings day −1 ). Our results show V. cholerae is subject to protozoan control and capable of utilizing multiple proliferation pathways in the marine environment. These findings suggest food web effects play a significant role controlling this pathogen's proliferation in coastal waters and should be considered in predictive models of disease risk.